Rural clean energy access: Accelerating climate resilience - Ringler, Claudia; Belete, Alebachew Azezew; Mathetsa, Steven Matome; Uhlenbrook, Stefan (International Food Policy Research Institute, 2022)
Globally, the energy sector accounts for almost three-quarters of total greenhouse gas (GHG) emissions and is thus responsible for the majority of adverse climate change impacts on rural livelihoods, including growing water, energy, and food insecurity and environmental degradation. According to a recent report from the Intergovernmental Panel on Climate Change, annual investments of US$2.4 trillion (2010 dollars) in energy systems are needed to limit global warming to 1.5°C. Such investments would support decarbonizing the largest polluters and improving energy efficiency. More and cheaper clean energy technologies and greater energy efficiency are equally critical for accelerating access to energy in underserved rural areas in ways that promote ecosystem health and inclusivity.